Identification of molecular phenotypic descriptors of breast capsular contracture formation using informatics analysis of the whole genome transcriptome. Issue 5 (13th August 2013) - Kyle, Daniel J. T.; Harvey, Alison G.; Shih, Barbara; Tan, Kian T.; Chaudhry, Iskander H.; Bayat, Ardeshir
Abstract Breast capsular contracture formation following silicone implant augmentation/reconstruction is a common complication that remains poorly understood. The aim of this study was to identify potential biomarkers implicated in breast capsular contracture formation by using, for the first time, whole genome arrays. Biopsy samples were taken from 18 patients (23 breast capsules) with Baker Grade I–II (Control) and Baker Grade III–IV (Contracted). Whole genome microarrays were performed and six significantly dysregulated genes were selected for further validation with quantitative reverse transcriptase polymerase chain reaction and immunohistochemistry. Hematoxylin and eosin was also carried out to compare the histological characteristics of control and contracted samples. Microarray results showed that aggrecan, tissue inhibitor of metalloproteinase 4 (TIMP4), and tumor necrosis factor superfamily (ligand) member 11 were significantly down‐regulated in contracted capsules; while matrix metallopeptidase 12, serum amyloid A 1, and interleukin 8 (IL8) were significantly up‐regulated. The dysregulation of aggrecan, tumor necrosis factor superfamily (ligand) member 11, TIMP4, and IL8 was validated by quantitative reverse transcriptase polymerase chain reaction (p < 0.05). Immunohistochemistry confirmed an increased protein expression for IL8 and matrix metallopeptidase 12 in contracted capsules (p < 0.05), and decreased protein expression of TIMP4 (p < 0.05). This study has shown, for the first time, a number of unique biomarkers of significance in capsular contracture formation. IL8 and TIMP4 may serve as potential key diagnostic, therapeutic, and prognostic biomarkers in capsular contracture formation.